PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT PARAGON TECHNOLOGY AND INNOVATION DEPARTEMEN PABRIK DI JATAKE TANGERANG - Kurniawati, Anggi; Irawati, Laila (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to determine the effect of leadership style and work environment on employee performance at PT Paragon Tecchnology And Innovation Factory Departement at Jatake Tangerang. The research method used this research is quantitative research. The population used in this study were employees of PT Paragon Tecchnology And Innovation Factory Departement at Jatake Tangerang.. The sampling method used by the author in this study is the saturated sample method, where the sample is the employees of PT Paragon Tecchnology And Innovation Factory Departement at Jatake Tangerang, totaling 53 employees. The data collection method used in this research is primary data. The primary data taken is the data from the answers of the respondents, amounting to 53 respondents. The results of this study indicate that leadership style a partial effect on employee performance at PT Paragon Tecchnology And Innovation Factory Departement at Jatake Tangerang as evidenced by the value of tcount > ttable or (3,853 > 2,007). This is also strengthened by the value of Sig. < 0.05 or (<0.001 < 0.05). The work environment has a partial effect on employee performance at PT Paragon Tecchnology And Innovation Factory Departement at Jatake Tangerang as evidenced by the value of tcount > ttable or (4,170 > 2,007). This is also reinforced by the value of Sig.<0.05 or (<0.001 < 0.05). leadership style and work environment have a simultaneous effect on employee performance at PT Paragon Tecchnology And Innovation Factory Departement at Jatake Tangerang as evidenced by the value of Fcount > Ftable or (122,631 > 3.18), this is also strengthened by the value of Sig. < 0.05 or (<0.001 < 0.05).